Implementasi Efektivitas Pembelajaran Luar Jaringan di SDN 070977 Kota Gunungsitoli melalui Program Kampus Mengajar Angkatan 3: THE TEACHING CAMPUS PROGRAM FORCE 3 - Lestari Sihaloho, Wika Mawar; Napitupulu, Fenty Debora; Sinaga, Samuel Juliardi; Harefa, Afore Tahir; Harefa, Sadarniwati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
One of the programs from the Merdeka Campus is the Teaching Campus Program which is implemented and led directly by the Ministry of Education and Culture which aims to improve the quality of teaching in Indonesia in the field of literacy & numeracy, assisting technology and school administration and teachers. The schools that are the target locations of this Teaching Campus Program are schools that are still underdeveloped in the aspects of literacy & numeracy, technological adaptation, and administration, therefore students who participate in the Teaching Campus Program will be very helpful in the learning process in schools that still lagging behind in these 4 aspects, one of which is SDN 070977 Gunungsitoli. Students will be involved in being responsible for helping to improve 4 aspects (literacy, numeracy, technology & administration) in the target schools, but not only those 4 aspects that are a concern for Teaching Campus students, but also help in increasing student interest in learning while directing students Pancasila character which is also the responsibility of the Teaching Campus students. The results of student participation in the Teaching Campus program are students can better understand and cultivate empathy and are more sensitive to social problems or the surrounding community, develop insight, character and also soft skills possessed by students, add to a relationship, create experiences that are different from others. world of lectures, fostering student motivation to participate in improving the quality of education in Indonesia